2017
DOI: 10.1111/jvp.12399
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of ceftiofur sodium in equine pregnancy

Abstract: Eleven pregnant pony mares (D270-326) were administered ceftiofur sodium intramuscularly at 2.2 mg/kg (n = 6) or 4.4 mg/kg (n = 5), once daily. Plasma was obtained prior to ceftiofur administration and at 0.5, 1, 2, 4, 8, 12, and 24 hr after administration. Eight pony mares were re-enrolled in the study at least 3 days from expected foaling to ensure steady-state concentrations of drug at the time of foaling. Mares were administered ceftiofur sodium (4.4 mg/kg, IM) daily until foaling. Parturition was induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Similar half-lives (p = .406) were calculated in cats following a single intravenous and subcutaneous injection (11.29 and 10.69 hr, respectively). Longer half-live (18.1 hr) was reported for ceftiofur sodium in neonatal calves (Woodrow et al, 2016); however, shorter ones were reported in pregnant pony mares (ranging from 2.91 to 4.1 hr; Macpherson et al, 2017) and sheep (in the range of 4.87-7.75 hr; Craigmill et al, 1997). These inconsistencies may be due to the differences in eating habits and/or physiological status.…”
Section: Fernandezmentioning
confidence: 98%
See 1 more Smart Citation
“…Similar half-lives (p = .406) were calculated in cats following a single intravenous and subcutaneous injection (11.29 and 10.69 hr, respectively). Longer half-live (18.1 hr) was reported for ceftiofur sodium in neonatal calves (Woodrow et al, 2016); however, shorter ones were reported in pregnant pony mares (ranging from 2.91 to 4.1 hr; Macpherson et al, 2017) and sheep (in the range of 4.87-7.75 hr; Craigmill et al, 1997). These inconsistencies may be due to the differences in eating habits and/or physiological status.…”
Section: Fernandezmentioning
confidence: 98%
“…The pharmacokinetics profiles of ceftiofur have been determined in horses (Collard et al, 2011;Edwards, Khalfan, Jacobson, Pirie, & Raidal, 2017;Macpherson et al, 2017;Meyer et al, 2009), cattle (Foster, Jacob, Warren, & Papich, 2016;Gorden et al, 2018;Jaglan et al, 1990;Kang et al, 2018;Okker et al, 2002;Wang et al, 2018;Woodrow, Caldwell, Cox, Hines, & Credille, 2016), water buffalo (Nie et al, 2016), camels (Goudah, 2007), goats (Courtin, Craigmill, Wetzlich, Gustafson, & Arndt, 1997;Fernandez-Varon, Carceles-Garcia, Serrano-Rodriguez, & Carceles-Rodriguez, 2016;Waraich, Sidhu, Daundkar, Kaur, & Sharma, 2017), sheep (Craigmill, Brown, Wetzlich, Gustafson, & Arndt, 1997;Nagel, Beltran, Molina, & Althaus, 2012;Rivera-Garcia et al, 2014), elephants (Dumonceaux, Isaza, Koch, & Hunter, 2005), pigs (Sparks et al, 2017;Xiong et al, 2018), avian species (Tell et al, 1998), and fish (Khalil, Shaheen, & Abdou, 2016). Among different species, ceftiofur shared some similar pharmacokinetics behaviors, such as relatively poor distribution, but quick and complete transformation to its active metabolites, desfuroylceftiofur (DCE), and desfuroylceftiofur conjugates (DCEC).…”
mentioning
confidence: 99%
“…Practitioners should consult culture and sensitivity results and consider use of first line antimicrobials, or local therapies, before considering treatment with ceftiofur. In contrast to support for treatment of endometrial infection, ceftiofur is not useful for treating placentitis in mares 83,84 …”
Section: Ceftiofur Pharmacokinetics and Pharmacodynamics In Horsesmentioning
confidence: 99%
“…In contrast to support for treatment of endometrial infection, ceftiofur is not useful for treating placentitis in mares. 83,84 5.6 | Use of ceftiofur for Lyme disease A full discussion of the complex disease processes that occur with Lyme disease is beyond the scope of this review. However, as ceftiofur has been recommended by some practitioners for the treatment of Lyme, we have included results of one study utilising ceftiofur treatment.…”
Section: Use Of Ceftiofur For Reproductive Infectionsmentioning
confidence: 99%